THE CHARACTERISTICS OF MENTAL HEALTH IN ELDERLY PEOPLE - Shafiyeva, Elnara; Murotmusaev, Komiljon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article is about an experimental psychological study of the mental health of 152 elderly people between the ages of 55 and 92 years. To achieve this goal, a special battery of techniques was selected. The results showed that 1) the mental health status of the elderly population may be considered normal; 2) Elderly people who receive a personal income from work, play sports, have hobbies and actively pursue activities suited to their age, and participate in the public life of the country are in good mental health; 3) The mental health status of elderly people who live in the suburbs or in nursing homes and who are employed in industries that require a high level of intelligence is worse than that of other elderly people. Elderly people living with their spouses have the best mental health status. 4) A negative attitude of elderly people toward disease and their environments can adversely affect their mental health, but a harmonious attitude does not significantly affect the mental state of elderly people.